Labeling Genetically Engineered Food in the United States: Suggestions for a New Approach - A. Bryan Endres (Laws, 2013)
The Federal Food, Drug, and Cosmetic Act (FFDCA) provides that a food is misbranded if the label accompanying the product is false or misleading in any particular. Congress provided minimal guidance to assist the FDA in making these determinations. When challenged, courts have granted substantial deference to FDA’s various interpretations of what constitute a material fact. However, when confronted with the regulatory question of whether or how to label products derived from genetically engineered (GE) crops, the FDA adopted a narrow reading of the statute that focused on changes in the product itself, rather than the act of genetic engineering. Only those GE products that possessed characteristics significantly different from their conventional counterparts would require labels. This “process versus product” distinction in food labels lies at the heart of the FDA’s resistance to repeated calls for mandatory labeling of foods derived from genetic engineering. Consumer interest in GE food, according to the agency, is not a material fact to trigger mandatory labeling under the statute. In contrast to its approach to GE labels, the agency has long required (since 1966) process-based labels for foods treated with irradiation. As recently as 1986, the FDA affirmed that materiality of information under it misbranding analysis is not limited to product safety or even the abstract worth of the information, but whether consumers view the information as important and whether the omission of a labeling statement would mislead the consumer. Accordingly, mere consumer interest can give rise to a mandatory labeling regime under the FFDCA. In the irradiation context, whole foods and single-ingredient products treated with irradiation must bear a label indicating the process. The irradiation of components in a multi-ingredient food product, however, need not bear a label. This distinction between processed, multi-ingredient and whole or single-ingredient foods provides a potential pathway for the agency to revise its approach to mandatory GE labeling. Exempting highly processed, multi-ingredient foods from a labeling regime would minimize traceability and segregation-generated disruptions in the commodity supply chain, thereby minimizing potential compliance costs, while also empowering consumers to express their preferences for non-GE whole and single-ingredient food products.